The Nagorno-Karabakh war: disputes over the concepts of 'victim' and 'genocide' in the present time (Tempo e Argumento, 2021)
This article aims at analyzing the idea of ‘victim’ and the uses of the concept of ‘genocide’ involving Armenians and Azerbaijanis in the Nagorno-Karabakh conflict. How do the parties mobilize these ideas in order to sustain their political demands regarding that territory and to delegitimize the aspirations of the other? The political leveraging of massacres and genocides for the purpose of raising international support for a cause is important to understand in this regard. We analyze the positions of Armenian and Azerbaijani leaders on the unfrozen conflict between September 27 to November 10, 2020